European Association of Urology Guidelines on Male Sexual and Reproductive Health: 2021 Update on Male Infertility - Minhas, Suks; Bettocchi, Carlo; Boeri, Luca; Capogrosso, Paolo; Carvalho, Joana; Cilesiz, Nusret Can; Cocci, Andrea; Corona, Giovanni; Dimitropoulos, Konstantinos; Gül, Murat; Hatzichristodoulou, Georgios; Jones, Thomas Hugh; et al. (European urology, 2021)
The European Association of Urology (EAU) has updated its guidelines on sexual and reproductive health for 2021. To present a summary of the 2021 version of the EAU guidelines on sexual and reproductive health, including advances and areas of controversy in male infertility. The panel performed a comprehensive literature review of novel data up to January 2021. The guidelines were updated and a strength rating for each recommendation was included that was based either on a systematic review of the literature or consensus opinion from the expert panel, where applicable. The male partner in infertile couples should undergo a comprehensive urological assessment to identify and treat any modifiable risk factors causing fertility impairment. Infertile men are at a higher risk of harbouring and developing other diseases including malignancy and cardiovascular disease and should be screened for potential modifiable risk factors, such as hypogonadism. Sperm DNA fragmentation testing has emerged as a novel biomarker that can identify infertile men and provide information on the outcomes from assisted reproductive techniques. The role of hormone stimulation therapy in hypergonadotropic hypogonadal or eugonadal patients is controversial and is not recommended outside of clinical trials. Furthermore, there is insufficient evidence to support the widespread use of other empirical treatments and surgical interventions in clinical practice (such as antioxidants and surgical sperm retrieval in men without azoospermia). There is low-quality evidence to support the routine use of testicular fine-needle mapping as an alternative diagnostic and predictive tool before testicular sperm extraction (TESE) in men with nonobstructive azoospermia (NOA), and either conventional or microdissection TESE remains the surgical modality of choice for men with NOA. All infertile men should undergo a comprehensive urological assessment to identify and treat any modifiable risk factors. Increasing data indicate that infertile men are at higher risk of cardiovascular mortality and of developing cancers and should be screened and counselled accordingly. There is low-quality evidence supporting the use of empirical treatments and interventions currently used in clinical practice; the efficacy of these therapies needs to be validated in large-scale randomised controlled trials. Approximately 50% of infertility will be due to problems with the male partner. Therefore, all infertile men should be assessed by a specialist with the expertise to not only help optimise their fertility but also because they are at higher risk of developing cardiovascular disease and cancer long term and therefore require appropriate counselling and management. There are many treatments and interventions for male infertility that have not been validated in high-quality studies and caution should be applied to their use in routine clinical practice. All infertile men require urological assessment and are at risk of cardiovascular mortality and several cancers. There is low-quality evidence supporting several empirical fertility treatments and the efficacy of these therapies needs to be validated in large-scale randomised controlled trials.